Numerical analysis of the echo obtained by radio echo sounder (III) (abstract) - Hoshiyama, Mitsuo; Izumi, Tatsuji; Nishitsuji, Akira; Wada, Makoto; Mae, Shinji; Kusunoki, Kou (1985)
P(論文) departmental bulletin paper